The great empires of the ancient world - Harrison, Thomas 1969- (J. Paul Getty Museum, 2009)
A team of internationally renowned scholars surveys the major imperial powers of the ancient world, from 1600 b.c. to a.d. 500, and ranging geographically from the ancient Mediterranean to East Asia. The authors investigate the nature of empires-including Egypt, Rome, Babylonia, Persia, India, and China-and their legacies in the modern age. Highlights include fascinating character profiles of great rulers such as the warrior pharaohs Thutmose and Rameses of Egypt, the self-obsessed First Emperor of China, who desperately tried to cheat death, and the brilliant Roman emperor Augustus, who created the most powerful empire the world had ever seen. Special illustrated sections, called "Witness to Empire" bring these civilizations to life in the words of their leaders and inhabitants. Not only will this book appeal to scholars and students, but its accessible text and wealth of illustrations will also feed the popular interest in this subject matter reflected in the recent success of films, television series, and museum exhibitions showcasing ancient cultures.